(untitled) (Analysis in Theory and Applications, 2012)
In the present paper, we obtain estimations of convergence rate derivatives of the q-Bernstein polynomials B_n(f,q_n;x) approximating to f'(x) as n→∞ which is a generalization of that relating the classical case q_n = 1. On the other hand, we study the convergence properties of derivatives of the limit q-Bernstein operators B_∞( f,q;x) as q→ 1^−.